SNP and Haplotype Interaction Models Reveal Association of Surfactant Protein Gene Polymorphisms With Hypersensitivity Pneumonitis of Mexican Population - Gandhi, Chintan K.; Chen, Chixiang; Amatya, Shaili; Yang, Lili; Fu, Chenqi; Zhou, Shouhao; Wu, Rongling; Buendía-Roldan, Ivette; Selman, Moisés; Pardo, Annie; Floros, Joanna (Frontiers in Medicine, 2021)
Background: Hypersensitivity pneumonitis (HP) is an interstitial lung disease caused by inhalation of common environmental organic particles. Surfactant proteins (SPs) play a role in innate immunity and surfactant function. We hypothesized that single nucleotide polymorphisms (SNPs) or haplotypes of the SP genes associate with HP. Methods: Seventy-five HP patients caused by avian antigen and 258 controls, asymptomatic antigen exposed and non-exposed were enrolled. SNP association was performed using logistic regression analysis and SNP-SNP interaction models. Results: Based on odds ratio, regression analyses showed association of a) rs7316_G, 1A3 (protective) compared to antigen exposed; b) male sex, smoking, rs721917_T and rs1130866_T (protective) compared to non-exposed controls with HP; c) compared to antigen exposed, 25 interactions associated with HP in a three-SNP model; d) compared to non-exposed, i) rs1136451 associated with increased, whereas rs1136450 and rs1130866 associated with lower HP risk, ii) 97 interactions associated with HP in a three-SNP model. The majority of SNP-SNP interactions associated with increased HP risk involved SNPs of the hydrophilic SPs, whereas, the majority of interactions associated with lower HP risk involved SNPs of both hydrophilic and hydrophobic SPs, e) haplotypes of SP genes associated with HP risk. Conclusions: The complexity of SNPs interactions of the SFTP genes observed indicate that the lung inflammatory response to avian antigens is modulated by a complex gene interplay rather than by single SNPs.